Pengaruh Kesadaran Wajib Pajak Terhadap Preferensi Risiko Sebagai Variabel Moderasi - Oktafiana Akmal; Zulia Hanum; Widia Astuty (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This stludy aims tlo examine andl analyze thle eflfect of taxplayer awarelness, tax klnowledge anld tax sanctions on individual talxpayer compliance with risk preference als a modlerating variablle at KPlP Pratama Medan Timur. The compliance rate of individuall taxpayers lat KPP Plratama Timur will decrease in 2022 by 85%. The type of research in this study is associative quantitative using data collection techniques with survey methods using questionnaires at KPlP Prlatama Mleldan Timur lJl. Suklamulia lNo. 17 A , Kelc. Medan Maimun, Indlonesia The methodl of deterlmining the slample with the slovin formula. The population of this research is 150,440 ltaxpayers while the rlesearch samplel is 100 relspondents. The data is processed using the SElM method wlith the help lof the Smart PLS alnalysis tool. Tlhe results of thlis study ilndicate that: (1) Taxlpayer awarenelss, tax knowledge and tax sanctions affect taxpayer compliance; (2) Risk preference does not moderate thel influence lof taxpayer lalwareness on taxplayer compliance and Risk preference moderates the influence of tax knowledge and tax sanctions on taxpayer compliance. For this reason, lit is hoped thatl KPP Pratamal Medan Timurl will further increase taxpayer awareness beyondl the ldesired standards so thatl later it willl be ablel to influencel taxpayers tol increase taxpayer lcompliance.